Mental health during the first wave of COVID-19 in Canada, the USA, Brazil and Italy. (1st June 2022) - Turna, Jasmine; Patterson, Beth; Goldman Bergmann, Carolina; Lamberti, Nina; Rahat, Maryam; Dwyer, Heather; Francisco, Ana Paula; Vismara, Matteo; Dell'Osso, Bernardo; Sideris, Beth; Van Ameringen, Michael
Abstract: Background: The mental health (MH) burden on healthcare practitioners (HCPs) is emerging as a significant cost of the pandemic, although few studies have compared the MH of HCPs in different countries. Methods: A link to an online survey was posted in the Spring of 2020 which included questions regarding perceived impact of the pandemic; current MH symptom severity and impairment was evaluated using validated scales. Results: Overall, 1315 individuals (74% female, mean age: 42.9 + 16.4) in Canada, the United States, Brazil and Italy completed the survey. Nearly 26% met diagnostic thresholds for GAD and MDD; Italian respondents reported the lowest rates of disorder. Except for Canada, non-HCPs in each country reported higher symptom severity than HCPs. Amongst the HCPs, Canadian HCPs reported the highest rates of anxiety and depression as well as increases in alcohol and cannabis use, lower levels of perceived emotional support and more worry about themselves or their loved ones contracting COVID-19. Conclusion: Despite key infrastructural and COVID-19 mortality differences between the countries, the MH effects appeared to be quite similar. HCPs, with the exception of Canada, reported less impact on their mental health compared to the general population, suggesting resilience in the face of adversity. Key points: Rates of current mental health disorders were similar across Canada, the USA and Brazil but lower in Italy, yet much higher than pre-pandemic rates Non-Healthcare Practitioners (HCPs) reported significantly higher severity on all MH scales in the overall sample. This was consistent within the USA, Brazil and Italy, however in Canada, HCPs reported higher anxiety, depression and stress symptom severity compared to Canadian non-HCPs. Canadian HCPs reported significantly higher anxiety and depression symptom severity than all other countries Canadian HCPs also reported significantly greater increases in alcohol and cannabis use, lower levels of perceived emotional support and more worry about themselves or their loved ones contracting COVID-19 compared to HCPs in the other countries.